Overview of Counselling Approaches to Stem Domestic Violence among Intimate Partners (Journal of Guidance and Counselling Studies, 2025)
Domestic violence disrupts individual lives and fractures communities, jeopardizing societal peace. This research explores the effectiveness of various counselling approaches in mitigating domestic violence and fostering community peace. The paper delves into the prevalent types of domestic violence and their impact on individuals, families, and the wider social fabric. Besides, the paper identified - Physical abuse, Emotional abuse, Verbal abuse, Sexual abuse, Intimate Partners Violence (IPV) and Economic abuse as most prevalent examples of domestic violence. It then critically examines a range of counselling approaches, including cognitive-behavioral therapy, psychodynamic therapy, and couples therapy. The analysis considers the strengths and limitations of each approach in addressing the root causes of domestic violence, empowering victims, and facilitating healthy behavioural patterns within relationships. Furthermore, the research explores the potential of these counselling approaches to foster community peace. It examines how effectively interventions can transform societal attitudes towards violence, promote healthy relationship models, and empower families and communities to identify and address domestic violence. The research employs a critical review methodology, drawing on scholarly literature, relevant data, and case studies to evaluate the efficacy of counselling approaches in curbing domestic violence and fostering community peace. The findings contributed valuable insights for policymakers, social workers, and mental health professionals working to create safer and more peaceful families and communities.